The mediating role of virtuousness in human resource management and job outcomes - Pires, L. (2018)
In this study, we explore the role of organizational virtuousness (OV) as a mechanism through which human resource management practices (HRMP) affect employee outcomes. We propose that HRMP lead to higher levels of organizational citizenship behaviors and affective commitment by stimulating OV. In a sample of 525 workers, from 22 stores of a retailing company, we found evidence that HRMP predicts OV, in turn predicting members’ citizenship behaviors and affective commitment. By suggesting this new mediator, this study contributes to a better understanding of the causal chain linking HRMP and performance.